Seminar Parenting Untuk Meningkatkan Kesadaran Pentingnya Membentuk Karakter Anak Berbasis Religius di Era Society 5.0 - Ully Hidayati; Rosti Rosti; Sri Hariati; Sartika G.P; Andi Saadillah; Ayu Rahayu (Journal Of Human And Education (JAHE), 2023)
In the current turbulent era of Society 5.0, the challenges in shaping children's character are increasingly complex. Parenting seminars are one of the media to provide understanding, strategy, and insight to parents regarding the importance of integrating religious values ​​in their children's education. This article explains how parenting seminars can influence participants' knowledge, attitudes, beliefs, implementation, and expectations regarding the formation of religious character. By describing the results of the pretest and post-test, this article illustrates the significant improvement in all of these aspects after attending the seminar. It is hoped that this article can provide insight into the important role of parenting seminars in dealing with the dynamics of children's character education in the modern era which is influenced by technological developments and the values ​​of Society 5.0. Keywords: Parenting, Character Education, Society 5